A Foundation Stone Inscription from the Petrischule in St. Petersburg - Budaragina, Olga (Hyperboreus, 2017)
The article deals with the foundation stone inscription from the Petrischule, the oldest school in St. Petersburg. Text of the inscription in German and Latin was written by pastor of the Petrikirche J. W. Zuckmantel for the ceremony of laying of the foundation of the new school building on 11 May 1760. The Latin part is the earliest known Neo-Latin building inscription in St. Petersburg.